(untitled) (Bangladesh Journal of Agriculture, 2023)
This investigation was done to determine how various plant growth regulators such as benzyl adenine (BA) and indole-3-butyric acid (IBA) affected the in vitro plant regeneration of the black pepper plant. The largest number of shoots was produced when the shoot tips and nodal segments of black pepper were utilized as explants and inoculated in Murashige Skoog (MS) media supplemented with 1.5 mg/L BA. The treatment with 2.0 mg/L BA at 8 weeks after induction (WAI) produced the most leaves (3.2). In the 2.0 mg/L treatment of IBA, the greatest number of roots was regenerated. The treatment 2.0 mg/L BA + 2.0 mg/L IBA produced the highest results for shoot induction, shoot length, and overall leaf production when the effects of both hormones were combined. The same treatment also produced the highest proportion of root induction and longest roots. Regenerated plantlets survive at a 46.67% rate in a shaded building and at a 57.14% rate in the open air under bright sunlight. In order to produce black pepper on a big scale, an effective approach for in vitro regeneration of black pepper has been established. Bangladesh J. Agri. 2023, 48(2): 75-85